Fair and Empathetic Practices in Examining Suspects: A Forensic Psychology Review of the Mechanisms Applied by Satgas PPKS UGM - Yungsiana, Istiqomah; Prabandari, Yayi Suryo (Faculty of Psychology, Universitas Gadjah Mada, 2026)
The Task Force for the Prevention and Handling of Sexual Violence at Universitas Gadjah Mada (Satgas PPKS UGM) is an ad-hoc unit responsible for preventing and responding to sexual violence within the campus environment. Since its establishment, Satgas PPKS UGM has conducted a substantial number of examinations of suspects. This study aims to describe and analyze fair and empathetic practices in examining suspects, based on a forensic psychology review of the mechanisms implemented by Satgas PPKS UGM. Using a case study design, the research examines several suspect examinations conducted by Satgas PPKS UGM. The findings show that examinations are conducted by an Examination Committee. During the process, investigative interviews with suspects follow the PEACE model (Preparation and Planning, Engage and Explain, Account, Closure, and Evaluation), as specified in the Procedures Operating Standard (POS). From a forensic psychology perspective, these stages reflect the application of procedural justice and forensic interviewing principles, enabling examinations to be neutral, fair, and empathetic while minimizing cognitive bias among committee members. The results also indicate that several suspects provided reliable information and achieved the objectives of the examination. These findings highlight the importance of integrating forensic psychology principles into suspect examination procedures, as this approach may contribute to strengthening fair, empathetic, and accountable examination practices oriented toward restorative justice within the UGM environment.